MATHEMATICAL MODELING AS A TOOL USED FOR REAL ESTATE MARKET ANALYSIS - Mamonov К.; Goi, V.; Viatkin, R.; Tishchenko А. (Municipal economy of cities. Series: «Economy science», 2025)
It is determined that the formation of a modern system of relations regarding the use of real estate requires rethinking approaches to the assessment and analysis of its market. In this context, there is a need to use mathematical modeling tools for analyzing the real estate market. In addition, factors influencing the assessment of real estate are determined, taking into account the features of the regulation of valuation activities. The proposed directions of mathematical modeling for the analysis of the real estate market: formation and application of information and analytical support for mathematical modeling for the analysis of the real estate market; determination of factors influencing the use of real estate; development of a multi-level system of real estate valuation indicators; implementation of real estate valuation; establishment of cause-and-effect relationships between real estate valuation factors using methods and models of mathematical modeling; determination of correlation and determination coefficients; construction of mathematical models of the dependence between real estate use factors; determination of indicators of the adequacy of mathematical models; interpretation of the results obtained; formation of a quantitative basis for decision-making. As a result of the study, the directions and features of real estate analysis are determined, taking into account regional and cost parameters. Regional asymmetries that affect the level of real estate use are identified. Directions of mathematical modeling are proposed for the analysis of real estate, which affects the completeness and reliability of the formation of a quantitative basis for decision-making, regulation of valuation activities. To analyze the real estate market based on the results of mathematical modeling, geographic information systems are used, which provides the ability to determine changes in factors and implement monitoring procedures.